Advances in the Treatment of Ovarian Cancer Using PARP Inhibitors and the Underlying Mechanism of Resistance - Wang, Ling; Wang, Qi; Xu, Yangchun; Cui, Manhua; Han, Liying (Current drug targets, 2020)
The standard treatment for advanced ovarian cancer is cytoreductive surgery followed by cytotoxic chemotherapy. However, it has high risk of recurrence and poor prognosis. Poly(ADPribose) polymerase (PARP) inhibitors selectively target DNA double-strand breaks (DSBs) in tumor cells that cannot be repaired and induce the synthetic lethality of BRCA1/2 mutation cancers. PARP inhibitors are clinically used to treat recurrent ovarian cancer and show significant efficacy in ovarian cancer patients with homologous recombination repair (HRR) pathway defects. PARP inhibitors also have significant clinical benefits in patients without HR defects. With the increasingly extensive clinical application of PARP inhibitors, the possibility of acquiring drug resistance is high. Therefore, clinical strategies should be adopted to manage drug resistance of PARP inhibitors. This study aims to summarize the indications and toxicity of PARP inhibitors, the mechanism of action, targeted treatment of drug resistance, and potential methods to manage drug-resistant diseases. We used the term "ovarian cancer" and the names of each PARP inhibitor as keywords to search articles published in the Medical Subject Headings (MeSH) on Pubmed, along with the keywords "clinicaltrials.gov" and "google.com/patents" as well as "uspto.gov." The FDA has approved olaparib, niraparib, and rucaparib for the treatment of recurrent epithelial ovarian cancer (EOC). Talazoparib and veliparib are currently in early trials and show promising clinical results. The mechanism underlying resistance to PARP inhibitors and the clinical strategies to overcome them remain unclear. Understanding the mechanism of resistance to PARP inhibitors and their relationship with platinum resistance may help with the development of antiresistance therapies and optimization of the sequence of drug application in the future clinical treatment of ovarian cancer.